Pseudomonas Aeruginosa Vaccines - Shnawa, Ibrahim Mohamed Saeed (Vaccines and Vaccine Interference, 2023)
Pseudomonas aeruginosa holds the position of an emerging human pathogen. Based on this holdings an array of experimental laboratroy developed vaccines were made. Non-of which reached the rank of clinical approved for human walfare.